Examining patient choice and provider competition under the National Health Insurance Fund outpatient cover in Kenya: does it enhance access and quality of care? - Kazungu, J; Barasa, E; Quaife, M; Nonvignon, J (BioMed Central, 2024)
Background: While patient choice and provider competition are predicted to influence provider behaviour for enhancing access and quality of care, evidence on provider perceptions and response to patient choice and provider competition is largely missing in low-resource settings such as Kenya. We examined provider and purchaser perceptions about whether patient choice and provider competition influenced provider behaviour and enhanced access and quality of outpatient care in Kenya. Methods: We conducted a qualitative study to explore this across two purposefully selected counties. We conducted 15 in-depth interviews (IDIs) with health facility managers and National Health Insurance Fund (NHIF) staff across the two counties. We examined these across five areas summarised as either local market conditions or patient feedback following the Vengberg framework. Results: NHIF members’ choice of outpatient facilities compelled private and faith-based providers to compete for members while public providers did not view choice as a way of spurring competition. Besides, all providers did not receive any information regarding the exit of NHIF members from their facilities. Providers felt that that information would be crucial for their planning, especially in enhancing service accessibility and quality of care. Most providers ensured the availability of drugs, provided a wider range of services and leveraged on marketing to attract and retain NHIF members. Finally, providers highlighted their redesign of service delivery to meet NHIF members’ needs whilst enhancing the quality-of-care aspects such as waiting time and having qualified health workers. Conclusion: There is a need for NHIF to share NHIF members’ exit information with providers to support their service delivery arrangements in response to NHIF members’ needs. Besides, this study contributes evidence on patient choice and provider competition and their influence on access and quality of care from a low-resource setting country which is crucial as NHIF transitioned to the Social Health Authority.